2023
DOI: 10.1159/000527973
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and Delirium Tremens in Hospitalized Patients with Alcohol Dependence Syndrome

Abstract: <b><i>Introduction:</i></b> Due to the high rate of mortality, recognizing the contributing factors of alcohol-related delirium tremens (DT), which is the most severe form of alcohol withdrawal state (AWS) is pivotal in clinical settings. Previous studies suggested relationship between seasonality and other types of delirium; however, to our knowledge, this is the first empirical study which examined the role of seasonality in DT in alcohol dependence syndrome (ADS). <b><i>M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…24,[30][31][32][33][34][35] By demonstrating that the presence of DT has an explanatory role in developing ARS, our results support these observations. Moreover, although several reports have evaluated that various factors such as older age, male sex, high blood level of homocysteine, low platelet count, low potassium level, and psychiatric and somatic co-morbidities can be risk factors for developing DT, 19,36,[43][44][45] the interplay of the occurrence of ARS and DT has not been evaluated in detail. Some studies have suggested that the ARS in medical history can increase the risk of the development of DT via the kindling mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…24,[30][31][32][33][34][35] By demonstrating that the presence of DT has an explanatory role in developing ARS, our results support these observations. Moreover, although several reports have evaluated that various factors such as older age, male sex, high blood level of homocysteine, low platelet count, low potassium level, and psychiatric and somatic co-morbidities can be risk factors for developing DT, 19,36,[43][44][45] the interplay of the occurrence of ARS and DT has not been evaluated in detail. Some studies have suggested that the ARS in medical history can increase the risk of the development of DT via the kindling mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol dependence syndrome is a recurrent and chronic brain disease caused by central nervous system poisoning caused by habitual excessive drinking (23). On the one hand, alcohol dependence will damage the patient's physical and mental health, on the other hand, it will also bring great burden to the patient's family, and even cause family breakdown in severe cases, which will lead to a series of social problems (24).…”
Section: Discussionmentioning
confidence: 99%
“…These studies helped identify high-risk patients who developed DT. The demographic profile of these populations typically consisted of middle-aged males with comorbidities and a history of long-term alcohol abuse [40][41][42][43][44][45][46]. Efforts should be directed toward prevention, early intervention, and long-term treatment of alcohol dependence to reduce the burden of DT and associated complications.…”
Section: Discussionmentioning
confidence: 99%